A social network analysis of South Central Kansas Workforce Innovations in Regional Economic Development. Issue 1 (9th March 2015) - Dziadkowiec, Oliwier; Wituk, Scott; Franklin, Debra
Abstract : Purpose: – The purpose of this study is to evaluate the composition and strengths/weaknesses and major actors of a coalition of regional economic leaders in the composites participating in the Workforce Innovations in Regional Economic Development (WIRED) project aimed at supporting high-skilled and high-wage careers. Design/methodology/approach: – Social network analysis (SNA) was used to assess south-central (SC) Kansas WIRED coalition ( n = 81) based on three surveys question: Who do you know? Who do you communicate with? and Who do you collaborate with? All the surveys were administered online in two waves. Findings: – SC Kansas WIRED network has a strong core, well-defined periphery and is immune to key actor losses, which suggests that they are well developed and sustainable. The well-defined periphery positions the collaborative to reach out to resources outside of the network and innovation. Practical implications: – SC Kansas WIRED Leadership team used the SNA to identify opportunities for further collaboration and reach out to individuals and groups who are not engaged well with others but are positioned well for sparking innovation and bringing resources to the region. Originality/value: – There are few analytic resources to empirically examine coalitions/collaboratives and the human and economic resources embedded in them. The results of this study and the feedback from SC Kansas WIRED Leadership team suggests that SNA was very valuable in identifying areas for action or improvement of the SC Kansas WIRED collaborative and can be utilized for effective decision-making.